2022
DOI: 10.1098/rspb.2021.2500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic coupling of life-history and aerobic performance in Atlantic salmon

Abstract: A better understanding of the genetic and phenotypic architecture underlying life-history variation is a longstanding aim in biology. Theories suggest energy metabolism determines life-history variation by modulating resource acquisition and allocation trade-offs, but the genetic underpinnings of the relationship and its dependence on ecological conditions have rarely been demonstrated. The strong genetic determination of age-at-maturity by two unlinked genomic regions ( vgll3 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 113 publications
5
31
0
Order By: Relevance
“…Such inherent high coupling capacity of salmon with the late maturation genotype may indicate that they could be more vulnerable to low food conditions such as during winters in freshwater (52) or in the sea (53). In line with this, a lower aerobic scope at the whole animal level –indicating lower capacity for aerobic metabolism beyond self-maintenance– in juvenile salmon with the late maturation genotype was also found by Prokkola et al (19). Further, the lower coupling capacity of the late maturation genotype matches the distribution of salmon with contrasting age-at-maturity in the wild, where individuals maturing later spawn typically in larger rivers that are likely more environmentally stable.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Such inherent high coupling capacity of salmon with the late maturation genotype may indicate that they could be more vulnerable to low food conditions such as during winters in freshwater (52) or in the sea (53). In line with this, a lower aerobic scope at the whole animal level –indicating lower capacity for aerobic metabolism beyond self-maintenance– in juvenile salmon with the late maturation genotype was also found by Prokkola et al (19). Further, the lower coupling capacity of the late maturation genotype matches the distribution of salmon with contrasting age-at-maturity in the wild, where individuals maturing later spawn typically in larger rivers that are likely more environmentally stable.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, vgll3 early maturation genotype is linked to higher body condition in salmon (20). Therefore, adipose tissue processes could provide a functional basis of variation in age-at-maturity, and subsequently, potential evolutionary constraints (15, 19).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, the lack of difference in SMR prior to maturation or prior to a change in body condition does not support SMR of juvenile salmon as a mediator of vgll3 effects on age at maturity at this particular age and in these conditions. Finally, these results were supported by a parallel study using a different crossing design and juvenile salmon of larger body size (Prokkola et al, 2021) where no association between SMR and vgll3 genotype was found.…”
Section: Discussionsupporting
confidence: 54%
“…We initially planned to also measure metabolic rate under exhaustive swimming to obtain data on maximum metabolic rate (MMR), but had to abandon these trials as we were unable to motivate juvenile salmon of this age and size to do any exhaustive swimming, either by swim tunnel or by hand chasing. This behavior might be specific to this life stage, as we were eventually successfully able to exercise fish up to MMR by hand chasing in a parallel study using a cohort from the same year that was studied 1–2 summer months later when the fish had grown from 1 to 4 g (Prokkola et al, 2021). Besides supporting our finding on the lack of an association between SMR and vgll3 genotype, Prokkola et al (2021) found a significantly higher MMR and aerobic scope in vgll3*EE compared to vgll3 *LL individuals, indicating that vgll3 genotype does affect the metabolic phenotype, but does so by affecting traits related to MMR without affecting SMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation